How the Radio Industry Is Changing to Deal with Changes in The Advertising Landscape - Harliantara; Öztürk, Bahar (Jurnal Riset Komunikasi (JURKOM), 2025)
This study examines the changing radio station landscape in Indonesia, especially how radio stations are adjusting to the move from traditional to digital advertising methods. As a result, traditional radio commercials are having a challenging time, especially when compared to the exact targeting and tracking that digital platforms offer. This study addresses this issue using a qualitative approach, focusing on case studies and interviews with radio broadcasting experts from leading radio stations. The study highlights three main ways to update the radio. The first is media convergence, which means combining radio with digital tools such as streaming, podcasts, and social media. The second is revenue diversification, which seeks new ways to generate revenue, such as event sponsorships and brand partnerships. We now discuss content enhancement, which involves creating local and engaging content to build a loyal audience base. In the digital age, radio must transform into a vibrant multimedia orchestra to truly flourish. This platform provides unique value to both listeners and advertisers.